Drug resistance, serotypes, and phylogenetic groups among uropathogenic Escherichia coli including O25-ST131 in Mexico City - José Molina-López; Gerardo Aparicio-Ozores; Rosa María Ribas-Aparicio; Sandra Gavilanes-Parra; María Elena Chávez-Berrocal; Rigoberto Hernández-Castro; Hipólito Ángel Manjarrez-Hernández (Journal of Infection in Developing Countries)
Introduction: The increasing prevalence of uropathogenic Escherichia coli (UPEC) strains resistant to multiple antibiotics complicates the treatment of urinary tract infections (UTIs). This study aimed to analyze the antimicrobial resistance, serotypes, and phylogenetic groups among strains of E. coli isolated from outpatients with UTIs in Mexico City.